2012
DOI: 10.1039/c2cc16430b
|View full text |Cite
|
Sign up to set email alerts
|

Slow magnetic relaxation in a pseudotetrahedral cobalt(ii) complex with easy-plane anisotropy

Abstract: A pseudotetrahedral cobalt(II) complex with a positive axial zero-field splitting parameter of D = 12.7 cm(-1), as determined by high-field EPR spectroscopy, is shown to exhibit slow magnetic relaxation under an applied dc field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
155
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 287 publications
(179 citation statements)
references
References 28 publications
22
155
2
Order By: Relevance
“…For the tetrahedral Co II complex [(3G)Co II Cl] + (43, Fig. 15), a positive D value was unambiguously determined by HF-EPR spectroscopy with D = 12.7 cm -1 , E = 1.2 cm -1 , g z = 2.17 [64]. Analysis of the magnetization data yielded D = 11.4(1) cm -1 , which was consistent with the EPR set of parameters.…”
Section: Tetrahedral Geometrymentioning
confidence: 70%
“…For the tetrahedral Co II complex [(3G)Co II Cl] + (43, Fig. 15), a positive D value was unambiguously determined by HF-EPR spectroscopy with D = 12.7 cm -1 , E = 1.2 cm -1 , g z = 2.17 [64]. Analysis of the magnetization data yielded D = 11.4(1) cm -1 , which was consistent with the EPR set of parameters.…”
Section: Tetrahedral Geometrymentioning
confidence: 70%
“…The double well model holds up in the case of monometallic cobalt(II) SMMs with negative D values [9,[11][12][13][14][15][16][17][18][19], but the observation of similar behaviour in monometallic cobalt(II) complexes with positive D values [20][21][22] suggests that the picture is more complex. Indeed, slow relaxation in positive-D compounds is a phenomenon that is not yet fully understood-although attempts have been made to explain it [23,24].…”
Section: Introductionmentioning
confidence: 90%
“…In 2012, Long and colleagues 4 found that a mononuclear pseudo-tetrahedral Co II shows slow magnetic relaxation, that is, it behaves as an SMM, when a small static magnetic field is applied to it. The same or similar behaviour has thereafter been reported for a number of other Co II complexes [5][6][7][8][9] as well as for lineal Fe II complexes 10 .…”
mentioning
confidence: 99%